The need for details for object discrimination and mnemonic discrimination - Palmer, Justin M.; Rhodes, Aidan; Ryan, Lee (Frontiers in Cognition, 2025)
Both mnemonic discrimination and object recognition tasks rely on the utilization of subtle visual details. Successful mnemonic discrimination utilizes the subtle details of an event to orthogonalize highly similar episodic memories, whereas object discrimination is a memory-free skill that utilizes details in order to distinguish between similar stimuli simultaneously presented. Additionally, neuroimaging studies have implicated areas of the medial temporal lobe as important for both mnemonic discrimination and object discrimination, further suggesting that performance on these two tasks are related. However, relatively limited data assessing the relationship between these two processes exist in the literature. Seventy-one cognitively normal participants completed both the Mnemonic Similarity Task (MST) and an object discrimination task used previously by our lab. The MST displayed common objects on a white background and participants identified if the object presented was old, similar, or new compared to objects previously seen in the task. For the object discrimination task, participants were shown a pair of stimuli (blobs or squares) that varied in difficulty (hard or easy). Outcome measures included correct responses to similar objects on the MST (mnemonic discrimination) and proportion of correct matches for hard and easy blobs and squares (object discrimination). Mnemonic discrimination for similar objects were correlated only with hard blobs after correcting for age, sex, and performance on easy trials (r = 0.24). These results might suggest that difficulty with effectively using the subtle details to discriminate between similar objects likely have downstream consequences on mnemonic discrimination that also require the integration of multiple visual details.